Efficacy of Temozolomide therapy in patients with aggressive pituitary adenomas and carcinomas: a German survey - Elbelt, Ulf; Schlaffer, Sven-Martin; Buchfelder, Michael; Knappe, Ulrich Johannes; Vila, Greisa; Micko, Alexander; Deutschbein, Timo; Unger, Nicole; Lammert, Alexander; Topuzoglu-Müller, Tengü; Bojunga, Jörg; Droste, Michael; et al. (The journal of clinical endocrinology & metabolism, 2019)
Despite growing evidence that temozolomide (TMZ) therapy is effective for the treatment of aggressive pituitary tumors (APTs) or carcinomas (PCs), individual therapy decisions remain challenging.We therefore aimed to report on clinical characteristics leading to initiation of TMZ therapy and to add evidence on TMZ long-term effectiveness.Retrospective survey on TMZ treatment in patients with APTs or PCs. TMZ therapy was initiated in 47 patients (22 females) with APTs (n = 34) or PCs (n = 13). Mean age at diagnosis was 45 ± 15 years. The immunohistochemical subtypes were corticotroph (n = 20), lactotroph (n = 18), and nonfunctioning (n = 9) tumors. TMZ therapy started 8 years after initial diagnosis using a standard regimen (median 6 cycles) for the majority of patients.Long-term radiological response to TMZ after a median follow-up of 32 months with 4 patients still on TMZ therapy was tumor regression for 9 (20%), stable disease for 8 (17%), and tumor progression for 29 patients (63%) (outcome data available for 46 patients). Progression occurred 16 months after initiation of TMZ. Median estimated progression-free survival was 23 months. Disease stabilization and median progression-free survival did not differ between patients with APTs or PCs. Predictors of tumor response were not identified. Overall, TMZ was well tolerated.We performed a nationwide survey on TMZ therapy in patients with APTs and PCs. While early response rates to TMZ are promising, long-term outcome is less favorable. Prolonged TMZ administration should be considered. We were not able to confirm previously reported predictors of tumor response to TMZ.